A GUEST + A HOST = A GHOST. DRAMAS OF HOSPITALITY IN REBECCA WEST’S THE RETURN OF THE SOLDIER - Ravizza, Eleonora Natalia (Armenian Folia Anglistika, 2021)
First published in 1918, Rebecca West’s debut novel The Return of the Soldier focuses on a common trope in Great War Literature: the traumas of war and the difficulties of returning veterans to fit back in with everyday life. The story of the shell-shocked soldier Chris Baldry, who suddenly finds himself in a world which has aged 15 years beyond his memory, may be read as the unfolding of a multi-layered drama of hospitality, in which the host-guest continuum is constantly renegotiated. Chris’s memory erasure does not only turn him into a foreigner who does not recognize his wife or remember his dead son, but also forces his family members to question the role they have been playing in Chris’s life. His family equilibrium is shattered as his wife suddenly becomes a stranger to him, while his long-lost love, a working-class woman well below Chris’s social standards, become more important to him than anyone else. An analysis of the modernist techniques and stylistic features of the novel will allow me to address the concept of hospitality in relation to trauma and disease. The paper will show that The Return of the Soldier may be read not only as a critique of war, but also as a multi-perspective narrative on the precariousness of host-guest relationships. It will be argued that the “question-of-the-foreigner”, which Derrida addressed in his seminal essay Of Hospitality (2003) acquires new meanings when disease suddenly transforms a loved one into an “other” with whom communication seems to be interrupted. Hospitality may thus be regarded an unstable concept, in which identity and alterity are constantly renegotiated.
Keywords: hospitality; alterity; literature ethics; war narrative; trauma